3 - Une histoire particulière de la mondialisation : Technique, travail et industrialisation de la noix de cajou au Mozambique - Fernando Bessa Ribeiro (African Sociological Review, 2015)
Industrial processing of cashew nuts in Mozambique has undergone significant changes over the last thirty years, especially in the field of production techniques and conditions. The article examines these changes, focusing on the impacts they have created at a plant in southern Mozambique, built according to the World Bank project proposal. Using the data collected during several ethnographic surveys, the discussion seeks to demonstrate that the technical choice and organization of work is closely dependent on political and social struggles in production spaces. These, in turn, are very conditioned by the global political and economic dynamics, particularly in Mozambique supported by the international financial organizations. Without globalization, it is not possible to understand the managerial and technical changes that have been verified in this industry, which have very strong impacts on the organization of production and working conditions.